Transformation of internal logistics: with autonomous transportation - Larsson, Filip; Wernestrand, Axel (My University, 2023)
Automation in internal logistics is becoming more relevant for industries today. Ef ficiency and cost reduction is what gets talked about the most. But automation can also be ways to improve the accuracy and reliability in the logistics processes. Man ual logistics processes are usually the most accident prone processes and automation can be a good way to reduce the risks of accidents occurring, protecting the em ployees in the production. Autonomous Guided Vehicles (AGVs) or Autonomous Mobile Robots (AMRs) are used within many different industries for automating internal transport of material. As the name suggest an AGV requires guidance in form of sensors, wires or magnetic strips that are built into the facility. An AMR on the other hand is capable of navigating independently through the use of a software utilizing data from cameras, senors and scanners. The different vehicles receive an order, which is then processed and material is delivered to the chosen destination. The process of picking-up and delivering material varies, and is often specifically designed for the process. This thesis covers the different aspects related to evaluating the feasibility of im plementing an AGV or AMR into an small and medium-sized enterprise (SME) as a pilot project. While expanding their business the company Skandia Elevator AB (SE) is also interested in creating safer working environments, and utilizing their resources and competence for more value-adding processes as the internal transports increase. How could the implementation of an AGV or AMR not only yield benefits in terms of safety and economics, but also help increase sustainability. The process chosen in this study is the transportation of material between manual press brakes and high storage units. A repetitive work task currently performed manually by forklifts. As a backbone of the thesis the Define, Measure, Analysis, Improve and Control (DMAIC) methodology was chosen, an iterative process commonly prac ticed at SE. The framework was used throughout the study, except for the last two steps, Improve and Control which are beyond the scope of the project. From the results it was possible to identify that from an economical perspective the Return on investment (ROI) for this specific process will not meet the company’s require ments. There are great value to be found in terms of safety along with other aspects discussed in the thesis. The findings from this thesis provide valuable insights and lessons in the implementation of this digital technology. Based on the overall assess ment, it is recommended that SE continues its efforts to integrate AMR into their business operations.
Keywords: AGV, AMR, SME, DMAIC, ROI